Preventing new substance use behaviors in youth: evaluation of a two-year comprehensive program - Zerhouni, Oulmann; Loisy, Sandra; Bouthier, Renaud; Flaudias, Valentin (Frontiers in Psychology, 2024)
Introduction. The Avenir Santé Association implemented a comprehensive prevention program targeting the consumption of the emerging psychoactive substances ecstasy (MDMA), cannabidiol (CBD), and nitrous oxide (N2O). Methods. The program was evaluated through four actions: (i) training for association workers (n = 84) (ii) on-site student party interventions (n = 248), (iii) social network-based prevention (n = 186), and (iv) provision of prevention tools for party organizers (n = 148). Results. Results showed a significant increase in understanding of emerging substances among association workers, with a pre-training score of M = 15.76 (SD = 3.65) and a post-training score of M = 18.29 (SD = 2.50). Increased awareness and reflective attitudes toward substance use were observed among young people participating in field actions, with pre-and post-intervention scores for MDMA use intentions being M = 15.89 (SD = 4.60) and M = 19.17 (SD = 3.33), respectively. Similarly, awareness of CBD effects increased from M = 14.18 (SD = 4.14) to M = 17.60 (SD = 3.31). Exposure to Instagram posts on N2O led to more negative attitudes toward N2O among young people, with a significant change in scores from M = 8.16 (SD = 1.57) to M = 8.42 (SD = 1.26). However, exposure to a website providing information about emerging substances did not produce any significant effect. Discussion. In conclusion, this initiative underscores the usefulness of facilitator training, field interventions, and certain online information strategies for substance judgment and usage intentions. Future prevention programs can advantageously incorporate these actions.